THE CHEST VOICE FUNCTION IN THE CLASSICALLY TRAINED SOPRANO: A SURVEY OF SELECTED VOCAL PEDAGOGY TREATISES FROM THE SEVENTEENTH CENTURY THROUGH THE TWENTIETH CENTURY AND RECORDING ANALYSIS FROM 1900 TO THE PRESENT WITH DISCUSSION OF THE IMPLICATIONS FOR - (:unkn) unknown (My University, 2013)
The purpose of this research is to document the use of chest voice in sound recordings of sopranos from the early 1900s through the twentieth century and to survey the vocal pedagogy informing performance practice of chest voice throughout the twentieth century. The research includes a survey of the chest voice in vocal pedagogy treatises from the seventeenth century through the twentieth century, and the performance practice of singers throughout the twentieth century in regard to the use of chest voice. The research also includes recording practices as they pertain to the different time periods of sound recordings used in this study. Three singers from each recording era are documented in regard to their rise to fame, voice teachers, training, use of chest voice in recordings, and approach to singing. Three arias will be used to trace the use of chest voice throughout the different eras of recorded history to document changes in style and approach to chest voice singing. The arias are "Una voce poco fa" from Rossini's Il Barbiere di Siviglia, "Salce, Salce" from Verdi's Otello, and "Air des bijoux" (The Jewel Song) from Gounod's Faust. The views about the use of chest voice over the past four hundred years inform the modern vocal pedagogue in regard to the changes in methodology, ideology, and practice due to the advances in vocal science and technology used to explore the voice and its function. However, until the beginning of sound recording the only form of documented historical performance lay in the opinions of critics and those who wrote about the performers of their day. In the research of this document the archival recordings provide the impetus for comparing vocal pedagogy instruction with performance practice in the use of chest voice.
Keywords: Vocal music--History and criticism; Singing--Interpretation (Phrasing, dynamics, etc.)